The methodological struggles of racial profiling research: a causal question that automobile stop data has yet to answer - Fallik, Seth Wyatt (Criminal justice studies, 2019)
Automobile stop research finds that citizen race influences officer decision-making. Researchers, however, report methodological issues inhibiting them from drawing causal inferences about the existence of racial profiling. The purpose of this study is to deconstruct this field of inquiry through a causal lens to inform the next generation of scholarship. Through an analysis of automobile stop data, temporal ordering issues are exposed. Relating to association, most studies find that racial minorities are more likely to be searched, however, spuriousness issues continue to plague racial profiling studies as researchers rarely estimate departmental, passenger, vehicle, and temporal variables. To confront these issues, researchers are encouraged to engage in primary data collection and explore recent statistical innovations in their analytical strategies.